The Central value of the Rankin–Selberg L-Functions - Li, Xiaoqing (Geometric and functional analysis, 2009)
. Let f be a Maass form for SL which is fixed and u j be an orthonormal basis of even Maass forms for SL , we prove an asymptotic formula for the average of the product of the Rankin–Selberg L -function of f and u j and the L -function of u j at the central value 1/2. This implies simultaneous nonvanishing results of these L -functions at 1/2.